Atmospheric pressure plasma‐jet treatment of polyacrylonitrile‐nonwovens—Stabilization and roll‐to‐roll processing. Issue 37 (28th July 2022) - Hoffmann, Andreas; Rohrbach, Felix; Uhl, Matthias; Ceblin, Maximilian; Bauer, Thomas; Mallah, Marcel; Jacob, Timo; Heuermann, Holger; Kuehne, Alexander J. C.
Abstract: Carbon nanofiber nonwovens represent a powerful class of materials with prospective application in filtration technology or as electrodes with high surface area in batteries, fuel cells, and supercapacitors. While new precursor‐to‐carbon conversion processes have been explored to overcome productivity restrictions for carbon fiber tows, alternatives for the two‐step thermal conversion of polyacrylonitrile precursors into carbon fiber nonwovens are absent. In this work, we develop a continuous roll‐to‐roll stabilization process using an atmospheric pressure microwave plasma jet. We explore the influence of various plasma‐jet parameters on the morphology of the nonwoven and compare the stabilized nonwoven to thermally stabilized samples using scanning electron microscopy, differential scanning calorimetry, and infrared spectroscopy. We show that stabilization with a non‐equilibrium plasma‐jet can be twice as productive as the conventional thermal stabilization in a convection furnace, while producing electrodes of comparable electrochemical performance. Abstract :